GIS-based Multi-criteria evaluation using AHP for landslide susceptibility zoning in Chattogram Hill Districts, Bangladesh - Hafsa, Bibi; Zannat, Bustanul; Chowdhury, Md. Sharafat; Hossain, Saikat (The Jahangirnagar Review, 2024)
GIS-based multi-criteria approach for landslide susceptibility zoning, providing a comprehensive understanding of spatial vulnerability patterns. By integrating a diverse range of geospatial datasets, including variables like soil permeability, elevation, land use and land cover, rainfall distribution, and proximity to key features such as roads, fault lines, and streams, this approach provides a holistic assessment of factors influencing landslide occurrences in Chattogram Hill Districts (CHD). Through the implementation of the Analytical Hierarchy Process (AHP), which assigns appropriate weights to each criterion based on their relative importance and the weighted overlay tool within ArcMap integrates every factor of landslide susceptibility and generates a comprehensive susceptibility map. The map reflects the distribution of 25.48% in the low susceptible class, 71.71% in the moderate susceptible class, and 2.81% in the high susceptible class. The Area Under Curve (AUC) of the Receiver Operating Characteristic (ROC) is used to validate the landslide susceptibility zoning. The calculated value of AUC is 0.828, indicating an 83% success rate of landslide mapping. Identifying areas at higher risk of landslides, developing targeted strategies for disaster preparedness, and formulating land use policies that account for potential hazards can be possible.